(untitled) (Research, Society and Development, 2021)
Objective: To implement a training protocol on intrauterine device (IUD) insertion for resident physicians to improve women’s access to this method. Methods: The staff identified poor access to family planning, in Vila Lobato health center, specially to IUD, there were only 15 IUD insertions in 2015. This implementation research evaluated and identified the barriers of access to IUD use. Then, stakeholders and staff defined the access flow of patients to the health unit and, eventually, the training provided to resident physicians in gynecology and obstetrics (GO) and family medicine (FM). This is a retrospective cohort of the IUD insertions performed by residents between 2016 and 2018. Results : 252 copper IUDs were inserted from 2016 to 2018 and there was a progressive increase in the number of insertions (45 in 2016, 80 in 2017, and 126 in 2018). Thirty-four (16.4%) inadequate insertions and 15 (8.6%) expulsions were observed. There was no case of uterine perforation. Conclusion: The implementation of the protocol on IUD insertion for residents in the primary care setting increased the local number of IUD insertion and might be a strategy to improve the access to the contraceptive method.